Interplay between sugar and hormone signaling pathways modulate floral signal transduction - Matsoukas, Ianis G. (Frontiers in Genetics, 2014)
The juvenile-to-adult and vegetative-to-reproductive phase transitions are major determinants of plant reproductive success and adaptation to the local environment. Understanding the intricate molecular genetic and physiological machinery by which environment regulates juvenility and floral signal transduction has significant scientific and economic implications. Sugars are recognized as important regulatory molecules that regulate cellular activity at multiple levels, from transcription and translation to protein stability and activity. Molecular genetic and physiological approaches have demonstrated different aspects of carbohydrate involvement and its interactions with other signal transduction pathways in regulation of the juvenile-to-adult and vegetative-to-reproductive phase transitions. Sugars regulate juvenility and floral signal transduction through their function as energy sources, osmotic regulators and signalling molecules. Interestingly, sugar signalling has been shown to involve extensive connections with phytohormone signalling. This includes interactions with phytohormones that are also important for the orchestration of developmental phase transitions, including gibberellins, abscisic acid, ethylene and brassinosteroids. This article highlights the potential roles of sugar-hormone interactions in regulation of floral signal transduction, with particular emphasis on Arabidopsis thaliana mutant phenotypes, and suggests possible directions for future research.